Circulating microparticle subpopulation in metabolic syndrome: relation to oxidative stress and coagulation markers - Zahran AM (Dove Medical Press, 2019)
Asmaa M Zahran,1 Sohair K Sayed,2 Heba A Abd El Hafeez,2 Walaa A Khalifa,3 Nahed A Mohamed,4 Helal F Hetta5,6 1Department of Clinical Pathology, South Egypt Cancer Institute, Assiut, Egypt; 2Department of Clinical Pathology, Faculty of Medicine, Assiut University, Assiut, Egypt; 3Department of Internal Medicine, Faculty of Medicine, Assiut University, Assiut, Egypt; 4Department of Medical Biochemistry, Faculty of Medicine, Assiut University, Assiut, Egypt; 5Department of Medical Microbiology and Immunology, Faculty of Medicine, Assiut University, Assiut, Egypt; 6Department of Internal Medicine, University of Cincinnati College of Medicine, Cincinnati, OH, USA Background: Circulating microparticles (MPs) contribute to the pathogenesis of atherothrombotic disorders and are raised in cardiovascular diseases. Herein, we aimed to investigate the effect of moderate metabolic abnormalities in an early stage of metabolic syndrome (MetS) on the level of MP subpopulations and to study relationships between MP subpopulations and both oxidative stress and coagulation markers. Methods: Flow cytometry used to evaluate circulating MPs subpopulations in 40 patients with an early stage MetS and 30 healthy controls. ELISA was used to quantify plasminogen activator inhibitor type 1/tissue plasminogen activator (PAI-1/TPA) while plasma glutathione peroxidase (GPx) activity was measured spectrophotometrically. Results: Total MPs were significantly elevated in MetS (P<0.001). Glutathione peroxidase and PAI1/TPA activity was significantly increased in subjects with MetS (P<0.001). Waist circumference, diastolic blood pressure, and total cholesterol positively influenced levels of total MPs, platelet-derived microparticles, and endothelium-derived microparticles. Fasting blood glucose, cholesterol, triglycerides, and low-density lipoprotein positively influenced the coagulation factors (TPA, PAI1). However, high-density lipoprotein negatively influenced platelet-derived MPs and factors associated with fibrinolysis (TPA, PAI1). Conclusion: Elevated circulating MPs are associated with MetS abnormalities, oxidative stress and coagulation factors and may act as early predictor of metabolic syndrome with risk of cardiovascular disease. Keywords: circulating microparticles, metabolic syndrome, oxidative stress, coagulation, CVD